Human rights and development in Bangladesh : exploring the challenge for democratic governance - Abdul Quddus, S. M. (s.n, 2013)
Human rights are considered to be necessary for freedom, democratic governance and of course the maintenance of a reasonable quality of life in a particular state or society. In this study, we have analyzed the nature and dynamics of human right situation in the contemporary context in Bangladesh and try to figure out the causes and consequences of human right violation for democratic governance in the country